4D surface seismic monitoring the evolution of a small CO2 plume during and after injection: CO2CRC Otway Project study. Issue 5 (2nd September 2020) - Popik, Sofya; Pevzner, Roman; Tertyshnikov, Konstantin; Popik, Dmitry; Urosevic, Milovan; Shulakova, Valeriya; Glubokovskikh, Stanislav; Gurevich, Boris
Abstract : Time lapse seismic is a vital component of the monitoring and verification of virtually any geosequestration project. Stage 2C of the CO2CRC Otway project is designed to test the limits of land 3D time-lapse (4D) seismic in the monitoring of small-scale CO2 injection. The 4D seismic monitoring program of Stage 2C of the Otway Project includes a baseline survey (BL); three monitor surveys (M1–M3) obtained during the injection of CO2 -rich gas into the saline aquifer at a depth of 1.5 km at the injection intervals of 5, 10, and 15 kt; and two post-injection surveys (M4 and M5), acquired one and two years after the end of injection. Reliable time-lapse changes among the 4D surveys were obtained using a buried receiver array. Analysis of the seismic cubes and attributes demonstrates that during and after injection the plume spreads laterally only in southeastern direction. The results demonstrate strong time-lapse signal corresponding to the injection level and the absence of any observed leakage into the overburden. The plume evolution is reliably observed and traced from M1 to M5 surveys with most of the changes occurring between the BL and M4 surveys.